Overview of A Nurse In Implementing 5 Moments of Hand Washing in the Prevention of Nosocomial Infection - Aeni, Qurrotul; Anggraeni, Rina; Nurwijayanti, Andriyani Mustika (Journal of Economics and Public Health, 2024)
Behaviors to prevent the spread of disease from person to person or from equipment to person can be carried out by placing a barrier between the microorganism and the individual (patient or health worker). The barrier can be physical effort in the form of washing hands. There are "5 moments" when health workers must perform hand hygiene. The aim of this research is to describe the implementation of the 5 moments of hand washing by nurses in the Bougenville ward of RSUD Dr. H. Soewondo Kendal. The type of research used is quantitative descriptive research. The sample in this study were nurses in the Bougenville room on the first and second floors of RSUD Dr. H. Soewondo Kendal as many as 31 respondents with a sampling technique using total sampling technique. The instruments used were questionnaires and observations. The questionnaire uses the standardized SPO KARS 2017. The research analysis used is univariate analysis. The results of research on the implementation of 5 hand washing moments, the majority of respondents always wash their hands before contact with patients, 23 (74.2%), nurses always wash their hands before carrying out aseptic procedures, 29 (93.5%), nurses always wash their hands after being exposed to body fluids. 29 patients (93.5%), 29 (93.5%) nurses always wash their hands after contact with patients, 29 (93.5%) nurses always wash their hands after contact with the patient's environment.